2017
DOI: 10.1161/hypertensionaha.116.08488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uric Acid–Lowering Agents on Endothelial Function

Abstract: Higher levels of serum uric acid are independently associated with endothelial dysfunction, a mechanism for incident hypertension. Obese/overweight individuals are more prone to endothelial dysfunction than their lean counterparts. However, the effect of lowering serum uric acid on endothelial dysfunction in these individuals has not been examined thoroughly. In this randomized, double-blind, placebo-controlled trial of nonhypertensive, overweight or obese individuals with higher serum uric acid (body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 20 publications
2
16
0
2
Order By: Relevance
“…Hyperuricemia is strongly associated with an increased risk of atherosclerosis and UA has also been shown to induce vascular endothelial dysfunction via oxidative stress and inflammatory responses (Puddu et al, 2012). However, whether elevated UA in the group of young males with high levels of android fat affects their endothelial function is uncertain because lowering UA fails to improve endothelial function (Borgi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia is strongly associated with an increased risk of atherosclerosis and UA has also been shown to induce vascular endothelial dysfunction via oxidative stress and inflammatory responses (Puddu et al, 2012). However, whether elevated UA in the group of young males with high levels of android fat affects their endothelial function is uncertain because lowering UA fails to improve endothelial function (Borgi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There remains an unanswered question, whether lowering uric acid can reverse the negative phenomena observed in PH, including endothelial injury. Feig showed that treatment with allopurinol can normalise blood pressure in hypertensive adolescents [25], but a recently published trial failed to prove a beneficial role of allopurinol in normalisation of endothelial dysfunction in adults with PH [26].…”
Section: Discussionmentioning
confidence: 99%
“…A few RCTs assessing the impact of uric acid lowering drugs on parameters of endothelial function showed no positive effect [ 155 , 156 ]. On the other hand, in a short-term study, allopurinol was shown to decrease blood pressure in young adolescents with newly diagnosed essential hypertension [ 157 ].…”
Section: Small Water-soluble Compoundsmentioning
confidence: 99%